Hydrophobicity-enhanced ferritin nanoparticles for efficient encapsulation and targeted delivery of hydrophobic drugs to tumor cells - Incocciati, Alessio; Kubeš, Jan; Piacentini, Roberta; Cappelletti, Chiara; Botta, Sofia; Bertuccini, Lucia; Šimůnek, Tomáš; Boffi, Alberto; Macone, Alberto; Bonamore, Alessandra (Protein science, 2023)
Ferritin, a naturally occurring iron storage protein, has gained significant attention as a drug delivery platform due to its inherent biocompatibility and capacity to encapsulate therapeutic agents. In this study, we successfully genetically engineered human H ferritin by incorporating 4 or 6 tryptophan residues per subunit, strategically oriented towards the inner cavity of the nanoparticle. This modification aimed to enhance the encapsulation of hydrophobic drugs into the ferritin cage. Comprehensive characterization of the mutants revealed that only the variant carrying four tryptophan substitutions per subunit retained the ability to disassemble and reassemble properly. As a proof of concept, we evaluated the loading capacity of this mutant with ellipticine, a natural hydrophobic indole alkaloid with multimodal anticancer activity. Our data demonstrated that this specific mutant exhibited significantly higher efficiency in loading ellipticine compared to human H ferritin. Furthermore, to evaluate the versatility of this hydrophobicity-enhanced ferritin nanoparticle as a drug carrier, we conducted a comparative study by also encapsulating doxorubicin, a commonly used anticancer drug. Subsequently, we tested both ellipticine and doxorubicin-loaded nanoparticles on a promyelocytic leukemia cell line, demonstrating efficient uptake by these cells and resulting in the expected cytotoxic effect.
Keywords: Ferritins; Doxorubicin; apoferritiny; Hydrophobic and Hydrophilic Interactions; Cell Line, Tumor; Nanoparticles; Drug Carriers; lidé; Antineoplastic Agents; protinádorové látky; tryptofan; nanočástice; Ellipticines; hydrofobní a hydrofilní interakce; Drug Delivery Systems; doxorubicin; Apoferritins; nosiče léků; Tryptophan; lékové transportní systémy; elipticiny; nádorové buněčné linie; ferritiny; Humans